Disease Diagnosis Expert System At Chili Plants Using Bayes Method - Susanti, Sri; Manahan, Olven (Information Technology and Science (ITScience), 2020)
The state of Indonesian is a country with a large part of the population earning a leaving in the agricultural sector, the agricultural sector in Indonesian contributis quite a lot in the development of long-term economic development. The role of the agricultural sector is as a source of producing ba sic foodstuffs, clothing and shalter, providing employment, and contributing to high national income. Chile is one of the agricultural commodities that are needed in daily life, Because this commodity has many benefits. Often Farmers detect disease that is wrong. To detect disease in precisely requires expert or expert in agriculture. The number of expert agricultural expert can not Overcome the problem of chili farmers, so it is needed a system where the system can help the work of an expert. In the expert system Dease In These chili diagnosing plant identifications using Bayes method in process. This expert system is implemented a in the form of a website the which aims to Facilitate access and use.